2004
DOI: 10.1111/j.1365-294x.2004.02162.x
|View full text |Cite
|
Sign up to set email alerts
|

Stocking impact and migration pattern in an anadromous brown trout (Salmo trutta) complex: where have all the stocked spawning sea trout gone?

Abstract: We examined polymorphism at seven microsatellite loci among sea trout (Salmo trutta) (n = 846) collected from three areas in the Limfjord (Denmark). We then assessed their potential population source by comparing, using a mixed stock analysis (MSA) Bayesian framework, their genetic composition to that of brown trout collected from 32 tributaries pooled into nine geographical regions (n = 3801) and two hatcheries (n = 222) used for stocking. For each of the three regional sea trout groups (western, central and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 44 publications
1
72
0
Order By: Relevance
“…Such effects are, however, expected to contribute little to allele frequency variation in marine organisms with extensive overlap between generations and the presumed very large effective population sizes. Our analysis comprised populations exhibiting lower differentiation than MSA studies in most other marine species (Wirgin et al 1997, Ruzzante et al 2000, Beacham et al 2008, Wennevik et al 2008) and approximately an order of magnitude lower than MSA studies in salmonids (Ruzzante et al 2004, Beacham et al 2005, Koljonen et al 2005, Smith et al 2005, Gauthier-Ouellet et al 2009). Using BAYES with data for 8 microsatellite loci typed in 26 Atlantic salmon populations, Koljonen et al (2005) reported that deviation between true and estimated single population contributions averaged 3% in a composite self-assignment test (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such effects are, however, expected to contribute little to allele frequency variation in marine organisms with extensive overlap between generations and the presumed very large effective population sizes. Our analysis comprised populations exhibiting lower differentiation than MSA studies in most other marine species (Wirgin et al 1997, Ruzzante et al 2000, Beacham et al 2008, Wennevik et al 2008) and approximately an order of magnitude lower than MSA studies in salmonids (Ruzzante et al 2004, Beacham et al 2005, Koljonen et al 2005, Smith et al 2005, Gauthier-Ouellet et al 2009). Using BAYES with data for 8 microsatellite loci typed in 26 Atlantic salmon populations, Koljonen et al (2005) reported that deviation between true and estimated single population contributions averaged 3% in a composite self-assignment test (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…MSA has been applied widely in anadromous salmonids (e.g. Ruzzante et al 2004, Beacham et al 2005, Koljonen et al 2005, Smith et al 2005, Gauthier-Ouellet et al 2009, Miller et al 2010), but in spite of the method's large potential for determining spatially and temporally explicit migratory behaviour, relatively few studies have yet been conducted in marine fishes (Waples & Naish 2009). One of the reasons for this paucity is that the generally modest levels of differentiation among marine populations (e.g.…”
mentioning
confidence: 99%
“…Similar MCMC analyses have been used to estimate stock composition and rookery contribution in other marine turtles and fishes (Fernandez et al 2002;Fillatre et al 2003;Herwerden et al 2003;Luke et al 2004;Ruzzante et al 2004). We also test the hypothesis that large rookeries in close geographic proximity to juvenile aggregations contributed more individuals to those populations than would be expected, given their relative size and geographic proximity.…”
Section: Introductionmentioning
confidence: 99%
“…Natural selection against domesticated fish and their descendants is generally assumed to be strong and may involve juvenile survival (McGinnity et al 2003), marine survival and return rate (McGinnity et al 2003;Ruzzante et al 2004) and spawning competition (Fleming et al 2000). However, in the case of the Skjern River selection against domesticated trout has not overcome the rate of 'immigration' because of stocking, as evidenced by the high and permanent admixture proportions of domesticated trout.…”
Section:    mentioning
confidence: 99%